ANALISIS WACANA PERCAKAPAN SIARAN PASAR SENGGOL CEPET PAYUNE RADIO POP FM SEMARANG - Mohamad Syaefudin; Maksum Suparman (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This research aims to explain (1) the speaking analysis using Dell Hymes SPEAKING theory; (2) the concept of adjacent pairs (3) turn to speak in a conversation broadcast "Senggol Market" Pop Radio FM Semarang. The research method uses descriptive qualitative approach. With a source of research data taken with see-recording techniques. Once that is done the transcription of the conversation. Conversation analysis conducted by (1) the analysis of the theory SPEAKING said component; (2) the concept of adjacency pair (3) turn-taking. The results showed three things. First, the theory SPEAKING is able to disclose the components of said broadcast radio promotion "Senggol Markets " Secondly, the adjacent pair of speech broadcaster and the caller forms a cohesive kewacanaan in a repeating pattern, deletion to build four speech acts illokusi "commanding, asking / giving information". The kewacanaan koherensif is done by answering questions in the order of the speech turn normally and well within the context of a typical owned broadcast program "Senggol Market" is. Third, there are 14 distribution patterns turn to speak using the random sequence applies sometimes adjust the speech broadcaster